Efektivitas Dan Efisiensi Pelaksanaan Anggaran Belanja Badan Perencanaan dan Pembangunan Daerah (BAPPEDA) Kabupaten Jepara - Jalal Luddin; Riska Rahmawati; Suparwi (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This research was conducted to analyze the level of criteria for the effectiveness and efficiency of the implementation of the budget in the regional planning and development agency in Jepara Regency. The data used is secondary data obtained from supporting documentation and literature as well as the official website of BAPPEDA Jepara Regency using financial realization reports from 2017 to 2022. The analysis technique used is quantitative descriptive analysis. The results of the study show that the budget level of the regional planning and development agency in Jepara Regency is in the category of effective and efficient. Effectiveness has been carried out, with the results of the data indicating that the program that has been realized is close to the expected target. As for efficiency, it is proven by the direct expenditure budget each year that is used to run previously planned programs that do not approach the actual expenditure value.